2022
DOI: 10.1162/nol_a_00065
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Mediation of Age-Related Differences in Picture Naming Across Adulthood

Abstract: As people age, one of the most common complaints is difficulty with word retrieval. A wealth of behavioral research confirms such age-related language production deficits, yet the structural neural differences that relate to age-related language production deficits remains an open area of exploration. Therefore, the present study used a large sample of healthy adults across adulthood to investigate how age-related white matter differences in three key left-hemisphere language tracts may contribute to age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
(121 reference statements)
4
3
0
Order By: Relevance
“…One possible interpretation, therefore, is that the left FAT, is involved in the suppression of the speech actions. According to such view, the left FAT specializes for the selection and inhibition of speech motor plans, congruently with recent studies showing that the left FAT has a direct role in speech motor planning (e.g., Troutman et al, 2022; Zhong et al, 2022). Troutman et al (2022), showed that the microstructural properties of the left FAT correlated not only with picture naming times but also with the response times to a less demanding production task in which participants were asked to produce the word “picture” in response to any picture.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One possible interpretation, therefore, is that the left FAT, is involved in the suppression of the speech actions. According to such view, the left FAT specializes for the selection and inhibition of speech motor plans, congruently with recent studies showing that the left FAT has a direct role in speech motor planning (e.g., Troutman et al, 2022; Zhong et al, 2022). Troutman et al (2022), showed that the microstructural properties of the left FAT correlated not only with picture naming times but also with the response times to a less demanding production task in which participants were asked to produce the word “picture” in response to any picture.…”
Section: Discussionsupporting
confidence: 85%
“…According to such view, the left FAT specializes for the selection and inhibition of speech motor plans, congruently with recent studies showing that the left FAT has a direct role in speech motor planning (e.g., Troutman et al, 2022;Zhong et al, 2022). Troutman et al (2022), showed that the microstructural properties of the left FAT correlated not only with picture naming times but also with the response times to a less demanding production task in which participants were asked to produce the word "picture" in response to any picture. Zhong et al (2022) reported a direct association between the severity of speech apraxia and the level of damage of left FAT in stroke patients.…”
Section: The Left Fat and L2 Productionsupporting
confidence: 85%
“…Crucially, this network-level approach complements the conventional view that the age-related loss of integrity takes place along dorsoventral (Boban et al, 2022;Zahr et al, 2009) and antero-posterior gradients (Bennett et al, 2010;Boban et al, 2022). Indeed, our results reveal that the SLF (II/III) and thalamo-frontal pathways, often attributed with the largest age-related changes (Bonifazi et al, 2018;Hughes et al, 2012;Troutman et al, 2022), are part of heterogeneous WM networks bind together by callosal fibers: the posterior midbody (CC6) binds association pathways (SLF II and SLFIII/MLF; Net 5), and the rostrum and genu (CC1/2) bind anterior cortico-subcortical pathways (e.g., ATR, T PREF, FPT; Net 11). Temporally, the WM networks most affected by age (i.e., Net 16, 5, 11, 4) showed the largest microstructural alterations occurring from age 53 onwards.…”
Section: Discussionsupporting
confidence: 70%
“…At a structural or neuroanatomical level, our understanding of the white matter integrity that accompanies these midlife functional changes remains largely unexplored, despite recent research highlighting white matter degradation as an explanation for the onset of LP deficits (Kljajevic & Erramuzpe, 2019;Sánchez et al, 2023;Troutman et al, 2022;Yeske et al, 2021). Within the language network (Shekari & Nozari, 2023), microstructural integrity assessed via diffusion tensor-based metrics (e.g., fractional anisotropy, radial diffusivity) is associated with higher-order aspects of naming, such as lexico-semantic selection, notably along the left superior fasciculus (SLF III; Troutman & Diaz, 2020) and inferior longitudinal fasciculus (ILF; Kantarci et al, 2011;Stamatakis et al, 2011;Troutman & Diaz, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, white matter integrity has been associated with age-related differences in language among neurotypical adults (for a review, see Dick & Tremblay, 2012; Dick et al, 2014). In the realm of language production, greater naming success has been associated with higher fractional anisotropy (FA) values along the superior longitudinal fasciculus (SLF; Houston et al, 2019; Stamatakis et al, 2011; Troutman & Diaz, 2020; Troutman et al, 2022). Consistent with this, more frequent tip-of-tongue states are associated with lower FA in the left posterior SLF (Stamatakis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%